The Changing Landscape of Pediatric Low-Grade Gliomas: Clinical Challenges and Emerging Therapies - Guerreiro Stucklin, Ana S.; Tabori, Uri; Grotzer, Michael A. (Neuropediatrics, 2016)
Pediatric low-grade gliomas (PLGGs) are the most common brain tumors in children. Though histologically benign and associated with excellent outcome, patients with unresectable lesions—mostly young children with midline tumors—experience multiple progressions and are at increased risk for long-term neurological sequelae. PLGGs in children with underlying genetic predisposition syndromes—especially neurofibromatosis type 1 and tuberous sclerosis—have a distinct natural history and biology with important treatment implications. Given the complexity of medical issues, optimal management requires a large network of health care providers; treatment decisions must address both tumor control and potential side effects of the therapy. Current treatment strategies often fail to induce sustained tumor regression and many children require several lines of therapy, highlighting the need for novel therapies. Here, we review the current management of PLGG and discuss how new molecular targets—in particular alterations of the Ras/MAPK pathway—are rapidly changing our approach to PLGG.
Keywords: low-grade glioma; children; Ras/MAPK; NF1; tuberous sclerosis